THE INFLUENCE OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT TO EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AT PT. SEOILINDO PRIMATAMA BEKASI - Buchori Nahar; Harry Indratjahyo; Guswandi (The Institute of Academic Research and Publication (IARP), 2020)
This study aims to: 1) To find out and analyze the influence of organizational culture and organizational commitment to job satisfaction, 2) To know and analyze the influence of organizational culture and organizational commitment on employee performance, 3) To find out and analyze the effect of job satisfaction on employee performance, 4) To find out and analyze the influence of organizational culture and organizational commitment to employee performance through job satisfaction of PT. Seoilindo Primatama Bekasi. The study was conducted at PT. Seoilindo Primatama Bekasi with 73 research samples. The sampling technique uses saturated samples. The data analysis method uses descriptive analysis and quantitative analysis with path analysis. The results showed that: 1) there is an influence of organizational culture and organizational commitment to job satisfaction, 2) there is an influence of organizational culture and organizational commitment to employee performance, 3) there is an influence of job satisfaction on employee performance, and 4) there is no influence of organizational culture and commitment organization of employee performance through job satisfaction PT. Seoilindo Primatama Bekasi. This means that the direct effect is greater than the indirect effect, the variable job satisfaction cannot mediate between organizational commitment and job satisfaction on employee performance at PT. Seoilindo Primatama Bekasi.